2012
DOI: 10.1063/1.3679126
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics simulation of the regrowth of nanometric multigate Si devices

Abstract: We use molecular dynamics (MD) simulation techniques to study the regrowth of nanometric multigate Si devices, such as fins and nanowires, surrounded by free surfaces and interfaces with amorphous material. Our results indicate that atoms in amorphous regions close to lateral free surfaces or interfaces rearrange at a slower rate compared to those in bulk due to the discontinuity of the lateral crystalline template. Consequently, the recrystallization front which advances faster in the device center than at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 29 publications
2
18
0
Order By: Relevance
“…CMD simulations have reproduced the observed experimental behavior regarding the defected recrystallization of FinFET structures in Si [102], as shown in Fig. 8.…”
Section: Cmd Modelssupporting
confidence: 58%
See 2 more Smart Citations
“…CMD simulations have reproduced the observed experimental behavior regarding the defected recrystallization of FinFET structures in Si [102], as shown in Fig. 8.…”
Section: Cmd Modelssupporting
confidence: 58%
“…Stresses can be externally generated or appear as a result of the 2% volume expansion of amorphous Si with respect to crystal Si [108]. CMD simulations have shown that the anisotropic regrowth of the amorphous phase in thin film layers results in twin defects [102,109,110], and that when significant strains are present, a slow-down in zones with high shear strain produces the evolution of ledges that collapse and evolve into Frank partial loops [111].…”
Section: Atomistic Kmc Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in full agreement with the molecular dynamics simulations obtained for Si nanowires. 27 These two processes result in formation of (111) stacking fault defects as well as epitaxial recovery of the rest of the nanowire including preexisting defects. The fact that the majority of the newly formed stacking faults are pinned to the nanowire surface suggests that the surface plays a predominant role in defect formation.…”
Section: Due To the Drastically Limited Range Of Interactions Of Ga-imentioning
confidence: 99%
“…26 In comparison to planar substrates, it has already been predicted by molecular dynamics simulations that the recrystallisation process in nanowires can be largely influenced by the presence of interfaces which propagate the formation of stacking fault defects. 27 Simulations of the defect dynamics have also shown that such defects are pinned at the nanowire surface and can be a result of overlapping growth fronts.…”
Section: Introductionmentioning
confidence: 99%